Substrate Binding Specifically Modulates Domain Arrangements in Adenylate Kinase - Zeller, Fabian (Biophys J, 2015)
The enzyme adenylate kinase (ADK) features two substrate binding domains that undergo large-scale motions during catalysis. In the apo state, the enzyme preferentially adopts a globally open state with accessible binding sites. Binding of two substrate molecules (AMP + ATP or ADP + ADP) results in a closed domain conformation, allowing efficient phosphoryl-transfer catalysis. We employed molecular dynamics simulations to systematically investigate how the individual domain motions are modulated by the binding of substrates. Two-dimensional free-energy landscapes were calculated along the opening of the two flexible lid domains for apo and holo ADK as well as for all single natural substrates bound to one of the two binding sites of ADK. The simulations reveal a strong dependence of the conformational ensembles on type and binding position of the bound substrates and a nonsymmetric behavior of the lid domains. Altogether, the ensembles suggest that, upon initial substrate binding to the corresponding lid site, the opposing lid is maintained open and accessible for subsequent substrate binding. In contrast, ATP binding to the AMP-lid induces global domain closing, preventing further substrate binding to the ATP-lid site. This might constitute a mechanism by which the enzyme avoids the formation of a stable but enzymatically unproductive state.